The systemin receptor SYR1 enhances resistance of tomato against herbivorous insects - Wang, Lei; Einig, Elias; Almeida-Trapp, Marilia; Albert, Markus; Fliegmann, Judith; Mithöfer, Axel; Kalbacher, Hubert; Felix, Georg (Nature plants, 2018)
The discovery in tomato of systemin, the first plant peptide hormone 1 , 2 , was a fundamental change for the concept of plant hormones. Numerous other peptides have since been shown to play regulatory roles in many aspects of the plant life, including growth, development, fertilization and interactions with symbiotic organisms 3 – 6 . Systemin, an 18 amino acid peptide derived from a larger precursor protein 7 , was proposed to act as the spreading signal that triggers systemic defence responses observed in plants after wounding or attack by herbivores 1 , 7 , 8 . Further work culminated in the identification of a leucine-rich repeat receptor kinase (LRR-RK) as the systemin receptor 160 (SR160) 9 , 10 . SR160 is a tomato homologue of Brassinosteroid Insensitive 1 (BRI1), which mediates the regulation of growth and development in response to the steroid hormone brassinolide 11 – 13 . However, a role of SR160/BRI1 as systemin receptor could not be corroborated by others 14 – 16 . Here, we demonstrate that perception of systemin depends on a pair of distinct LRR-RKs termed SYR1 and SYR2. SYR1 acts as a genuine systemin receptor that binds systemin with high affinity and specificity. Further, we show that presence of SYR1, although not decisive for local and systemic wound responses, is important for defence against insect herbivory. Systemin was the first peptide hormone discovered in plants almost 30 years ago. Here, the receptor for systemin is finally identified and is shown to be important in the response against insect herbivores.